Exploring the Role of Teachers in Facilitating Communication and Social Interaction among Deaf Students: A Case Study at SLB-E Negeri Pembina Medan - Badai Mutiara Rezeki Nasution; Ismail Ismail (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study explores teachers' roles in educating hard-of-hearing students in communication and social interaction at SLB-E Negeri Pembina Medan. The main focus of this research is to understand how teachers enhance students' communication skills and social interactions through appropriate approaches, methods, and learning strategies. This research employs a qualitative case study approach, with data collection techniques through interviews, observations, and documentation. Research shows that teachers support hard-of-hearing students' social development by applying innovative teaching methods and creating an inclusive learning environment. Using visual aids and technologies such as images, videos, and sign language significantly contributes to creating an effective and enjoyable learning process for hard-of-hearing students.